Starch Biocryogel for Removal of Methylene Blue by Batch Adsorption - Tarawee Taweekarn; Worawit Wongniramaikul; Chanita Boonkanon; Chonthicha Phanrit; Wilasinee Sriprom; Wadcharawadee Limsakul; Wanchitra Towanlong; Chanadda Phawachalotorn; Aree Choodum (My University, 2022)
A green monolithic starch cryogel was prepared and applied for the removal of methylene blue (MB) using a batch system. The influence of various experimental parameters on MB adsorption was investigated. High removal efficiency (81.58 ± 0.59%) and adsorption capacity (34.84 mg g−1) were achieved. The Langmuir model better fitted the experimental data (determination coefficient (R2) = 0.9838) than the Freundlich one (R2 = 0.8542), while the kinetics of MB adsorption on the cryogel followed a pseudo-second-order model. The adsorption process was spontaneous and endothermic with an activation energy of 37.8 kJ mol−1 that indicated physical adsorption. The starch cryogel was used for MB removal from a wastewater sample collected from a local Batik production community enterprise in Phuket, Thailand, and a removal efficiency of 75.6% was achieved, indicating that it has a high potential as a green adsorbent for MB removal.
Keywords: Endothermic process; Methylene blue; Langmuir adsorption model; Adsorption and biosorption for pollutant removal